The Effectiveness of Ultrasound-Assisted Extraction on Antioxidative Properties of Bract Leaves of Globe Artichoke - Akdogan, Doruk; Peksel, Aysegul (ISTANBUL UNIV, 2023)
Objective: The antioxidant-rich artichoke bracts leaves are a particularly waste of the food industry. Thus, it would be possible to utilize a cheap and natural material, which is industrial waste, instead of synthetic antioxidants. The present study aimed to extract from the bract leaves of globe artichoke by ultrasound-assisted extraction and to evaluate their antioxidant activities. Materials and Methods: In this study, the effect of ultrasound-assisted extraction (UAE) on antioxidative properties was studied. The extracts were obtained from the leaves of the head part of the artichoke by using UAE and evaluated for their antioxidative properties. For this purpose, antioxidant activity methods were investigated for different extraction times. The results obtained were compared with standard antioxidants. Results: The results obtained from this study showed that the shorter extraction time resulted in higher antioxidative properties. Accordingly, in plant extracts prepared by UAE-1, the highest total phenolic content value (193.80 mu g pyrocathecol equivalent/mg extract), the highest total flavonoid content value (254.13 mu g catechin equivalent/mg extract), the highest total chlorophyll content value (10.68 mu g/mL) and carotenoid (0.57 mu g/mL) were found. Similarly, UAE-1 extracts showed the best results in terms of free radical scavenging activity. Also, the 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity of UAE-1 (89.09%) was determined to be higher than the standard antioxidant alpha-Tocopherol (85.68%) and very close to another standard antioxidant butylated hydroxyanisole (91.98%). Conclusion: UAE could be preferred instead of the traditional method (Soxhlet) as a shorter, eco-friendly, and low energy cost.
Keywords: Antioxidative properties; Ultrasound-assisted extraction; Plant extract; Cynara scolymus L.; Radical scavenging; Life Sciences & Biomedicine - Other Topics